Is Religion Natural? Boyle Lecture 2024 - Fergusson, David (Zygon, 2025)
A commitment to religion as natural has commanded widespread support in the history of theology and philosophy. This has often been used apologetically, whether through arguments for religious innatism or from a consensus gentium, neither of which now seems plausible. This article, originally delivered as the 2024 Boyle Lecture, explores these issues in conversation with recent work in the cognitive science of religion (CSR), where support can be found for religion as natural to our evolved condition. One upshot of this is that, if we are by nature disposed towards religion, then pace the standard secularization thesis, it is unlikely to disappear. Yet, while acknowledging the success of CSR, several theological questions are raised about its explanatory reach. The essay concludes by suggesting where a complementarity of scientific and theological description might lead in this domain.